Engaging in community music an introduction - Higgins, Lee 1964-; Willingham, Lee
Engaging in Community Music: An introduction focuses on the processes involved in designing, initiating, executing and evaluating community music practices. Designed for both undergraduate and graduate students, in community music programmes and related fields of study alike, this co-authors textbook provides explanations, case examples and "how-to" activities supported by a rich research base.